Aryl Hydrocarbon Receptor Antagonism Promotes Hematoendothelial Development from Human Pluripotent Stem Cells - Angelos, Mathew G.; Kim, Anna; Kaufman, Dan S. (Blood, 2015)
The aryl hydrocarbon receptor (AHR) is an evolutionarily conserved transcription factor originally characterized for its role in mediating biological responses to carcinogenic environmental agents. Recent studies have elucidated the importance of AHR-dependent signaling for normal physiological function in the absence of environmental ligands, most notably the development of Th17 cells, regulatory T-cells, and natural killer (NK) cells from human peripheral blood and umbilical cord blood. Additionally, AHR is highly expressed in hematopoietic stem/progenitor cells (HSPCs), and antagonism of AHR using small molecules results in a marked expansion of umbilical cord blood-derived HSPCs suitable for clinical transplantation. It remains unclear what role, if any, AHR plays during early human hematoendothelial development. We hypothesized inhibition of AHR-mediated cell signaling could promote early human hematopoietic cell development. To model human hematopoiesis, we employed a xenogeneic-free and chemically defined in vitro method to differentiate human embryonic stem cells (hESCs) into endothelial and hematopoietic cells. qRT-PCR analysis demonstrated a significant increase in AHR (13.36±5.52 fold change, p<0.05, n=3) by Day 11 of differentiation relative to undifferentiated hESCs. CYP1A1 and CYP1B1, two downstream targets of AHR-mediated signaling, were similarly upregulated on Day 11 (27.90±6.17 fold change, p<0.05, n=3; 134.28±10.06 fold change, n=3, respectively). Increase in AHR expression mirrored the onset of early hematopoietic progenitor cell differentiation; CD34+ CD43+ and CD34+ CD41a+ cells were markedly increased by Day 12 of hematopoietic differentiation as assessed by flow cytometry (18.9%±3.22, p<0.01, n=7; 8.23±2.00, p<0.05, n=7, respectively). We next modified the relative activity of AHR signaling by differentiating hESCs in the presence of 2,3,7,8-tetrachlorodibenzo-p- dioxin (TCDD), a prototypical AHR agonist, or StemReginin-1 (SR-1), an AHR antagonist, and assessed its effects on hematopoietic progenitor cell production. Interestingly, we observed a significant increase in the appearance of both CD34+ CD31+ hematoendothelial cells in SR-1 treated hESCs relative to DMSO treated controls (17.63%±1.25, p<0.05, n=3 vs. 11.21±0.63, p<0.05, n=3) at Day 9. Later by Day 12, we also found approximately a two-fold expansion of CD34+ CD45+ hematopoietic progenitor cells in SR-1 treated hESCs relative to DMSO treated controls (16.35%±4.05, p<0.05, n=3 vs. 7.53±0.19, p<0.05, n=3). Treatment with TCDD reciprocally attenuated the development of CD34+ CD45+ progenitor cells at Day 15 relative to DMSO treated controls (3.99%±0.80 vs. 11.79%±1.41, p<0.05, n=3) and resulted in an expansion of terminally differentiated hematopoietic cells (CD34- CD43+: 84.5%±2.78 vs. 70.9±1.58, p<0.05, n=3; CD34- CD45+: 81.75%±1.75 vs. 71.95±2.35, p<0.05, n=3). We confirmed the functionality of the hematopoietic progenitor cells in each group by harvesting non-adherent cells at Day 12 and performing standard colony-forming assays. SR-1 treated cells yielded a 4-fold increase in the total number of colonies generated relative to DMSO treated control cells along with an increased proportion of CFU-M and CFU-GM. We also evaluated whether AHR antagonism could be used to promote NK cell differentiation from hESCs. Using previously optimized and defined NK cell differentiation conditions, we found SR-1 treatment caused an increase in CD56+ CD45+ NK cells relative to DMSO treated controls (26.4% vs. 19.7%, n=2) whereas TCDD treatment caused a decrease (6.7%, n=2). Work assessing how hematopoiesis from hESCs is affected using AHR gene knockouts developed from CRISPR/Cas9-mediated gene deletion is ongoing. Collectively, our results demonstrate AHR antagonism promotes early human hematoendothelial development and may be used as a potential molecular target to enhance hematopoietic cell production from human pluripotent stem cells for clinical applications. No relevant conflicts of interest to declare.